Effectiveness and safety of rotary and reciprocating kinematics for retreatment of curved root canals: a systematic review of in vitro studies - Simoes, Lucas Pinho; Reis-Prado, Alexandre Henrique dos; Emerenciano Bueno, Carlos Roberto [UNESP]; Diniz Viana, Ana Cecilia; Hungaro Duarte, Marco Antonio; Angelo Cintra, Luciano Tavares [UNESP]; Araujo Lemos, Cleidiel Aparecido; Benetti, Francine (Korean Acad Conservative Dentistry, 2022)
Objectives: This systematic review (register-osf.io/wg7ba) compared the efficacy and safety of rotary and reciprocating kinematics in the removal of filling material from curved root canals. Materials and Methods: Only in vitro studies evaluating both kinematics during retreatment were included. A systematic search (PubMed/MEDLINE, Scopus, and other databases, until January 2021), data extraction, and risk of bias analysis (Joanna Briggs Institute checklist) were performed. Efficacy in filling removal was the primary outcome. Results: The search resulted in 2,795 studies, of which 15 were included. Efficacy was measured in terms of the remaining filling material and the time required for this. Nine studies evaluated filling material removal, of which 7 found no significant differences between rotary and reciprocating kinematics. Regarding the time for filling removal, 5 studies showed no difference between both kinematics, 2 studies showed faster results with rotary systems, and other 2 showed the opposite. No significant differences were found in apical transportation, centering ability, instrument failure, dentin removed and extruded debris. A low risk of bias was observed. Conclusions: This review suggests that the choice of rotary or reciprocating kinematics does not influence the efficacy of filling removal from curved root canals. Further studies are needed to compare the kinematics safety in curved root canals.
Keywords: Curved root canals; Nickel-titanium instruments; Reciprocating; Retreatment; Rotary kinematics